Directional Sources and Listeners in Interactive Sound Propagation using Reciprocal Wave Field Coding - Chaitanya, Chakravarty R. Alla; Raghuvanshi, Nikunj; Godin, Keith; Zhang, Zechen; Nowrouzezahrai, Derek; Snyder, John (ACM Transactions on Graphics (SIGGRAPH 2020), 2020)
Everyday sources like voices and musical instruments radiate in a strongly directional manner. The radiated sounds propagate through complex environments undergoing scattering, diffraction, and occlusion before reaching a directional listener. For instance, someone speaking from an adjoining room will be heard loudest when they speak facing a common door, and their voice will be heard as coming through the door. Interactive sound propagation aims to render such audio cues in virtual worlds to deeply enhance the sense of presence. It is a tough problem: modeling, extracting, encoding, and rendering must all be done within tight computational resources. We present the first technique that can render such immersive wave effects in any complex game/VR scene. In particular, we can render directional effects from freely moving and rotating sources with arbitrary source directivity function. Spatial audio rendering can be performed as binaural via any head-related transfer function (HRTF), or through speaker panning. We show an integration of our interactive sound propagation system in Unreal Engine (TM). Our system's CPU performance is insensitive to scene complexity and angular source/listener resolutions.
(Equal contribution from first and second listed authors)